2013
DOI: 10.1038/ijos.2013.86
|View full text |Cite
|
Sign up to set email alerts
|

Role of sortase in Streptococcus mutans under the effect of nicotine

Abstract: Streptococcus mutans is a common Gram-positive bacterium and plays a significant role in dental caries. Tobacco and/or nicotine have documented effects on S. mutans growth and colonization. Sortase A is used by many Gram-positive bacteria, including S. mutans, to facilitate the insertion of certain cell surface proteins, containing an LPXTGX motif such as antigen I/II. This study examined the effect of nicotine on the function of sortase A to control the physiology and growth of S. mutans using wild-type S. mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 34 publications
2
43
0
Order By: Relevance
“…Unlike abp-A, the abp-B mutant strain retains the ability to bind to soluble amylase (29). abp-A, instead of abp-B, is the major protein for S. gordonii tooth surface binding (33), and the present study confirmed that the expression of abp-A was much higher than that of abp-B (Fig. 3).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Unlike abp-A, the abp-B mutant strain retains the ability to bind to soluble amylase (29). abp-A, instead of abp-B, is the major protein for S. gordonii tooth surface binding (33), and the present study confirmed that the expression of abp-A was much higher than that of abp-B (Fig. 3).…”
Section: Discussionsupporting
confidence: 77%
“…An SrtA mutant of S. gordonii demonstrated less biofilm and impaired binding ability (35). Previous studies in our laboratory demonstrated that sortase-defective S. mutans forms less biofilm than the wild type under the same nicotine treatment (33). The promotion effect of nicotine on S. gordonii srtA expression partially explains the increased biofilm formation in nicotine-treated groups.…”
Section: Discussionmentioning
confidence: 49%
“…WD = 8 mm; 15 Kv. nicotine [48]. This might explain why S. sanguinis biofilm exposed to nicotine (0.3, 3 and 30 μg/mL) enhanced carbohydrate levels in our study.…”
Section: Discussionmentioning
confidence: 64%
“…Each PCR reagent (25 μL) contained SYBR® Premix Ex Taq ™ II (RR820A; Takara Bio), cDNA samples (80 ng) and forward and reverse gene-specific primers (10 μM, 1 μL each). The qPCR was performed on CFX96 Real-Time System (C1000™ Thermal Cycler; Bio-Rad, Hercules, CA) using the same thermocycling conditions as in a previous study [35]. The 2 −ΔΔCt method was used to calculate gene expression fold change, and different gene expressions were normalized to the levels of 16S rRNA gene transcripts.…”
Section: Methodsmentioning
confidence: 99%